(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Objective: The aims and objective of this study to observe the improvement in Nocturnal Asthma symptoms and Quality of Life (QoL) with administration of once daily sustained release theophylline preparation. Background: Nocturnal symptoms are a common part of the asthma. Nocturnal asthma is defined by a drop in forced expiratory volume in 1 second (FEV1) of at least 15% between bedtime and awakening in patients with clinical and physiologic evidence of asthma, which may include improvement in QoL. Methodology: The patient with Chronic Persistent Asthma, both sex, age >18 to 50 years of age and preferably patients with nocturnal exacerbations were included in the study. All patients were diagnosed on the basis of clinical history, physical examination, chest X-ray and pulmonary function tests, in accordance with the clinical criteria for the diagnosis by the GINA. The recruitment period was between March 2017 and August 2017 Shaheed Suhrawardy Medical College Hospital, Dhaka. Results: It was observed that 65(92.85%) was found exacerbation free night and 5(7.15%) patients were found exacerbation with sustained release Theophylline. There are significantly improved qualities of life between 1st follow up to 2nd follow up, 3rd follow up and 4th follow up p<0.001 which was statistically significant. Spirometry test was gradually improved between 1st visit of FEV1 to 2nd, 3rd and 4th visit of FEV1, (p<0.001) that was statistically significant. Conclusion: Most of the patients were found exacerbation free night. There are significantly improved quality of life between 1st follow up to 2nd follow up, 3rd follow up and 4th follow up in Spirometry test. The value of FEV1 was gradually improve in the lst visit, 2nd, 3rd and 4th visit with sustained release Theophylline. J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 74-77